DEER Data Analysis Software: A Comparative Guide - Russell, Hannah; Cura, Robyn; Lovett, Janet E. (Frontiers in Molecular Biosciences, 2022)
Pulsed Dipolar Spectroscopy (PDS) Electron Paramagnetic Resonance (EPR) experiments are popular techniques to measure dipolar coupling and therefore nanometre-scale distances and distance distributions between paramagnetic centres. The most common experiment is Double Electron Electron Resonance (DEER, also known as PELDOR), which is a well-tested and documented experiment. Until recently there were few methods to analyze data, however this has changed of late. The current plethora of DEER analysis packages may appear overwhelming to a new practitioner of DEER. In this work, six of the most popular packages are reviewed. This includes a brief guide for getting started with the environments, and qualitative testing and comparison of each using both simulated and experimental DEER data.